أحاديث عدم دخول الطاعون إلى المدينة: دراسة حديثية موضوعية - صالح، سعد صبار (جامعة الأنبار - كلية العلوم الإسلامية, 2020)
شاءت إرادة الله تبارك وتعالى في العباد أن ينتشر بينهم في نهاية عام ٢٠١٩ م وباء خطير ومرض فتاك أسماه العلماء كوفيد ١٩ واشتهر لدى الناس باسم كورونا وكان من شأن هذا المرض الفتاك أن أصاب أعدادا غير قليلة من الناس في أكثر بلدان العالم. وكان من قدر الله تعالى أن دخل الوباء إلى مكة والمدينة وأصاب ساكنيها كما دخل في بلدان العالم الأخرى وهنا ظهرت نابتة من أعداء الإسلام وخصومه بل وعن بعض جهلة المسلمين وأشاعوا بين الناس من خلال بعض القنوات الفضائية أو وسائل التواصل الاجتماعي أو على مواقع الشبكة العالمية الإنترنيت، وأذاعوا أن وباء كورونا أظهر بما لا يقبل الشك كذب بعض الأحاديث النبوية التي نصت على أن الطاعون لا يدخل مكة والمدينة، وكنت مستغربا من صنيع هؤلاء المدعين وكيف أنهم استعجلوا الطعن قبل التمعن في التفكير وبذل الوسع لبيان السقيم من الصحيح بل هالني العجب وانتابتني الدهشة لقوم عالجوا أخطاء تفكيرهم وهوى قلوبهم وأحقاد صدورهم بوهم ظنوه حقا وخيال حسبوه واقعا، ولما رأيت الأمر بهذه الخطورة رأيت من الواجب علي أن أتناول الأحاديث الدالة على عدم دخول الطاعون المدينة دراسة حديثية موضوعية وبيان المراد منها وتجليتها بأوضح عبارة مستدلا على ذلك بأقوال علماء الدين المحققين ومعتمدا على آراء الأطباء المعاصرين. وهنا تكمن أهمية البحث. وجعلت هذا البحث بعد التوكل على الله تعالى في مقدمة وثلاثة مطالب وخاتمة. أما المقدمة فذكرت فيها سبب البحث وأهميته والمنهج الذي اتبعته في البحث، وأما المطلب الأول فذكرت فيه أحاديث الباب وتخريجها وبيان رواتها ودراسة أسانيدها والحكم عليها. وأما المطلب الثاني فقد جعلته في بيان معنى الطاعون والوباء لغة واصطلاحا وذكر الفرق بينهما، وأما المطلب الثالث: عدم ظهور الطاعون في المدينة تاريخيا، من مبعث الرسول صلى الله عليه إلى يومنا هذا مصداقا لحديثه عليه الصلاة والسلام ثم جاءت الخاتمة حيث بينت فيها أهم ما توصلت إليه من نتائج.
The will of God aimighty wanted the people to spread amang them at theend of the year 2019 A.D. a serious pandemic and a deadly disease that scientists called as covid – 19 and it was known to people in the name of corona and this deadly disease affected a large number of people in most countries of the world and it was Gods destiny almighty that the epidemic entered mecca and Almadina and affectad their inhabitants as it entered in other countries of the world, here aspite emerged from the enemies of Islam and its opponents and euen from some ignorawt muslims, They spread among the people througl some satellite channels or social media or on the websites of the world wide web end broadcast that the corona epidemic revealed with no doubt that some prophehic sayings which stated that the plague does not enter mecca and madina are untrue. The researcher is surprised from the sayings of these claimants and how they rushed to appeal before relying an thinking and exerting the effort to know the lie and the truth. I am surprised by people who dealt with the errors of their thinking and their hearts and the grudges of their chests. It was an illusion that they really thought and imagination they considered reality. when I saw the matter with this grauity, I took a decision to study this hadith wlich indicates that the plague does not enter Almadina by adopting modern analytical study to state what is meant by it and clarify it most clearty referring to the statements and inuestigations of religious scholars besides the opinions of contemporary doctors. Here lies the imeortance of the research which wnsists of the introduction and three sections and a conclusion. As for the introduction? I mentioned the aim of this research and its importance and the approach followed. In the first section I haue mentioned the hadiths of this topic and their narration loy their narrators. Also the study of the foundations and judgements on them are given. The second section explains ling uistically the meaning of the plague and pandemic. It also studies them idiomatically and the difference between them is giuen. concerning the third section, it concentrates on the fact that the plague his torically has not appeared in almadina from the period the prophet (peace and blessing be upon him) settled in it up to the present time in agreement with the hadith of the prophet. The most important results arriued at in this research haue been given in the conclusion. I have written this research with pure intention, so what was right is from God and what was wrong is mine since I am a human being who sins and does right things. our last prayer is that praise be to God , lord of the worlds
Keywords: الأحاديث النبوية -- الطاعون -- المدينة المنورة -- شرح الحديث